The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1103/physrevb.54.14066
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the α-Cr2O3(0001) surface: Anab initiototal

Abstract: The structure of the basal plane of the ␣ phase of Cr 2 O 3 has been investigated using periodic ab initio Hartree-Fock theory. The Cr-terminated surface, which is nonpolar but is charged, is found to be stable. However, a large-scale relaxation of the surface layer away from the ideal bulk-terminated structure has been found. The top layer Cr 3ϩ ions move inward toward the second-layer O 2Ϫ ions by nearly 50% of their original interlayer spacing. This results in a slight lowering of the Cr ionicity in the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 20 publications
5
44
2
Order By: Relevance
“…To reduce the effect of a polar surface, we would expect a large contraction for the outermost Cr layer toward to the bulk, which was confirmed by XPD data analysis. Theoretical studies [52,53] of the (0001) surfaces of bulk a-Cr 2 O 3 indicated a single Cr layer termination and a strong relaxation of this layer away from that of the bulk. In both the Hartree-Fock [52] and density functional Fig.…”
Section: Experimental Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To reduce the effect of a polar surface, we would expect a large contraction for the outermost Cr layer toward to the bulk, which was confirmed by XPD data analysis. Theoretical studies [52,53] of the (0001) surfaces of bulk a-Cr 2 O 3 indicated a single Cr layer termination and a strong relaxation of this layer away from that of the bulk. In both the Hartree-Fock [52] and density functional Fig.…”
Section: Experimental Discussionmentioning
confidence: 97%
“…The high Coulomb energy associated with each ionic point charge could explain the large relaxation expected for these oxide surfaces. Rehbein et al [52], assert that shielding of charged atoms dramatically decreases the total energy of surface when the Cr outermost layer relaxes toward the second layer formed by oxygen atoms, and conclude that the surface preferentially terminates in Cr ?3 . Our oxygen termination result might merely reflect the formation of a relatively weakly bound layer of oxygen at the surface due to the growth conditions described in Sect.…”
Section: Experimental Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Table IV 6,12,16 Although there are notable deviations from the LEED data, 6 we need to remember that the latter correspond to the actual surface termination but were fitted assuming the A (1 × 1) model.…”
Section: Appendix A: Surface Relaxationsmentioning
confidence: 99%
“…In particular, surfaces of magnetoelectric antiferromagnets such as Cr 2 O 3 possess an equilibrium surface magnetization, [1][2][3][4] making them suitable for use as active layers in electrically switchable magnetic nanostructures. 1 The Cr 2 O 3 (0001) surface has been a subject of many experimental [5][6][7][8][9][10][11] and theoretical 5,6,[12][13][14][15][16] studies, but its structure remains poorly understood. Low-energy electron diffraction (LEED) experiments for a thin Cr 2 O 3 (0001) film grown on a Cr (110) single crystal revealed an unusual reentrant structural phase transition, 5 in which the surface structure changes from 1 × 1 to √ 3 × √ 3 and back to 1 × 1 under cooling from room temperature to 150 K and then further down to 100 K. The origin of these phase transitions is not understood.…”
Section: Introductionmentioning
confidence: 99%